Measurement of Conductance of FeCl3 in Distilled Water at Different Temperature and Concentration - Yadav, Chandradip Kumar; Yadav, Brahamdeo (Rupantaran: A Multidisciplinary Journal, 2020)
Precise measurement of the conductivity of FeCl3 in distilled water at 303.15 and 308.15 K temperature were measured. The specific conductivities exhibited a sharp increase with increase in concentration within the concentration range investigated (0.001 to 0.100 mol per liter. The decrease in the conductance with decrease in concentration is due to decrease in the number of ion per unit volume of the solution. Also decrease in conductance with decrease increase in temperature due to decrease in the speed of the ions.